2008
DOI: 10.1111/j.1365-280x.1998.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Emmonsiosis of rodents in an agroecosystem

Abstract: Adiaspores of Emmonsia crescens were found in the lungs of 62·1% of 87 adult rodents from 10 windbreaks compared to only 8·2% of 184 adult rodents caught in 10 adjacent arable fields in South Moravia, Czechland. A significantly higher mean weight proportion of plant remnants (predominantly small roots) was present in the soil from windbreaks (0·74%) than from fields (0·24%). In addition, mean relative abundance of rodents was significantly higher in windbreaks than in fields, and the windbreak soil was more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some aspects of their saprobic and parasitic stages have led Emmonsia species to be considered close relatives of dimorphic fungi (Emmons & Ashburn 1942, Sigler 1996, Peterson & Sigler 1998. Their occurrence has been related to the agroecosystem and their highest abundance was observed in plant remnants and rodent burrows (Hubalék et al 1998). The presence of this fungus has been reported in domestic and wild rodents (Zlatanov & Genov 1975, Hubalék et al 1998, carnivores (Krivanec et al 1980) and armadillos (Santos 1999).…”
Section: Molecular Biology Has Demonstrated That P Brasiliensis Belomentioning
confidence: 98%
See 1 more Smart Citation
“…Some aspects of their saprobic and parasitic stages have led Emmonsia species to be considered close relatives of dimorphic fungi (Emmons & Ashburn 1942, Sigler 1996, Peterson & Sigler 1998. Their occurrence has been related to the agroecosystem and their highest abundance was observed in plant remnants and rodent burrows (Hubalék et al 1998). The presence of this fungus has been reported in domestic and wild rodents (Zlatanov & Genov 1975, Hubalék et al 1998, carnivores (Krivanec et al 1980) and armadillos (Santos 1999).…”
Section: Molecular Biology Has Demonstrated That P Brasiliensis Belomentioning
confidence: 98%
“…It must be considered that this phylogenetic group (Onygenales) includes the species E. parva and Emmonsia crescens that cause adiaspiromycosis, a localized lung infection of cosmopolitan distribution, both in wild animals and humans (Hubalék et al 1998). Some aspects of their saprobic and parasitic stages have led Emmonsia species to be considered close relatives of dimorphic fungi (Emmons & Ashburn 1942, Sigler 1996, Peterson & Sigler 1998.…”
Section: Molecular Biology Has Demonstrated That P Brasiliensis Belomentioning
confidence: 99%
“…With this definition, numerous unrelated species have been affiliated to the genus. Confusion has particularly been caused by reporting species of Emmonsia in the Onygenalean family Ajellomycetaceae comprising pulmonary colonizers of wild rodents, under the name Chrysosporium (Hubalek et al, 1998). In contrast, Chrysosporium species according to the current definition either reside as saprobes in habitats enriched with keratin such as bird feathers and animal hair when related to Onygenaceae (De Hoog et al, 2000; Hubalek, 2000), or cause skin infections in reptiles when affiliated to Nannizziopsiacea (Stchigel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that its occurrence is related to dense forest areas, with abundant plant remnants (53). Several works have reported the presence of this fungus in wild and domestic rodents, carnivores and armadillos (53)(54)(55)(56). Rodent burrows have been pointed out as the main habitats of the fungus since it is present in the soil and is frequently detected in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…As observed for the remaining dimorphic fungi of the order Onygenales, the soil seems to constitute the main habitat of Emmonsia spp. Studies have shown that its occurrence is related to dense forest areas, with abundant plant remnants (53). Several works have reported the presence of this fungus in wild and domestic rodents, carnivores and armadillos (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%